2018
DOI: 10.1080/14766825.2018.1447950
|View full text |Cite
|
Sign up to set email alerts
|

Urban heritage and cultural tourism development: a case study of Valletta’s role in Malta’s tourism

Abstract: Despite significant potential for cultural tourism, the predominant form of tourism in Malta is sun and sea. This paper evaluates Malta's potential for cultural tourism with a focus on Valletta, a fortified historic city that overlooks the Grand Harbour. Valletta's rich urban heritage and historic narrative makes it ideal for the development of a more cultureoriented tourism. The paper explores how, over more than half a century of tourism activity in Malta, culture and heritage retained a secondary role. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
(23 reference statements)
0
27
0
1
Order By: Relevance
“…The desire to move away from a beach resort tourism offer to one based on heritage and culture is only barely re ected in the data on tourists' motivations [57]. Despite an increase in absolute numbers, the proportion of culture and heritage tourists over the period 2007 and 2011 has remained stable, at around 15% of all holiday visits to Malta [58].…”
Section: Geoculture As Wellbeingmentioning
confidence: 99%
“…The desire to move away from a beach resort tourism offer to one based on heritage and culture is only barely re ected in the data on tourists' motivations [57]. Despite an increase in absolute numbers, the proportion of culture and heritage tourists over the period 2007 and 2011 has remained stable, at around 15% of all holiday visits to Malta [58].…”
Section: Geoculture As Wellbeingmentioning
confidence: 99%
“…Their findings showed that aesthetics value (heritage) perceived and appreciated by the elderly influenced the elderly's decision to travel to a particular place. Similar studies [29][30][31][32][33] explored the importance of heritage sites in attracting inbound tourists (including the elderly).…”
Section: Introductionmentioning
confidence: 95%
“…Postindustrial tourism can thus be metaphorically seen as a sort of bricolage experience (Judd, 2003), either tailor-made for affluent tourists, based on small-scale products available in urban space, or even assembled piece-by-piece by travellers with lower budgets who seek their own path of discovery. Cultural and creative industries intermingle with tourism attractions (Baptista et al, 2018;Jones, 2017), as part of urban competition strategies (Richards, 2014) and alternatives to conventional touristic products (Ebejer, 2019).…”
Section: Public Space and The Urban Territorialisation Of Tourismmentioning
confidence: 99%